The Effect of Black Sea Cucumber (Holothuria atra) Ethanolic Extract and Gel on Diabetic Ulcers in Rattus norvegicus Induced by Streptozotocin - Erika Nur Fanani; Roostantia Indrawati; Wienta Diarsvitri; Indri Ngesti Rahayu; Viranda Senora Permata; Nilam Cahya; Alifiah Wahyu Nur Fadilah (Majalah Biomorfologi, 2026)
Background:  Diabetic ulcer is a common complication of poorly controlled diabetes, often leading to chronic wounds and impaired healing. Black sea cucumber (Holothuria atra) is known to contain bioactive compounds, including saponins and flavonoids, which exhibit antidiabetic and wound-healing properties. Objective: To evaluate the therapeutic effect of ethanolic extract and gel formulations of Holothuria atra on diabetic ulcers in streptozotocin (STZ)-induced Rattus norvegicus. Materials and Methods: A randomized pre-test and post-test control group design was employed, involving 30 rats divided into five groups. Group C(-) served as the healthy control, while C(+) was a diabetic group treated with acarbose (4.5 mg/kg body weight) and 10% povidone-iodine. The experimental groups T1, T2, and T3 consisted of diabetic rats treated with Holothuria atra extract at doses of 50, 75, and 100 mg/kg body weight, respectively, along with corresponding topical gel concentrations (50%, 75%, and 100%) for 14 days. Ulcer healing was monitored by measuring wound closure, and data were analyzed using a one-way ANOVA test via IBM SPSS version 26.0 for Windows. Results: C(+) achieved the fastest wound closure by day 4, followed by T3 and T2 on day 5, and T1 on day 6. However, statistical analysis revealed no significant difference in ulcer healing between the groups (p = 0.56). Conclusion:  Holothuria atra extract orally and gel topically demonstrated comparable healing efficacy to standard treatment with acarbose and povidone-iodine, although the differences were not statistically significant. These findings suggest Holothuria atra has potential as a complementary therapy for diabetic ulcers.